Invisible architects of life: the influence of bacteria and fungi on hawksbill turtle nesting - Lam, Kai Yoon (Nanyang Technological University, 2025)
Microbial communities play a significant role in influencing the reproductive success of endangered sea turtles, yet their impacts remain poorly understood. This study investigates the fungal and bacterial communities associated with hawksbill turtle (Eretmochelys imbricata) nests in Singapore, with a focus on their relationship to hatching success. Samples were collected from eggshells, dead embryos, yolks, and surrounding sand, and analyzed using ITS and 16S rRNA gene amplificon sequencing. Hatching success across 30 nests varied widely, ranging from 9% to 98%, providing a robust dataset to evaluate microbial influences. Quantitative analyses revealed that unhatched eggshells exhibited higher DNA yields and greater amplification success than hatched eggshells, suggesting a greater microbial presence associated with reduced hatching success. Fusarium, a known turtle egg pathogen, showed a negative correlation with hatching success. In contrast, bacterial genera such as Pedobacter showed strong positive associations, indicating potential protective roles. Notably, Pedobacter has been known to possess antifungal activity, including against Fusarium, and in this study showed a negative correlation with Fusarium abundance. Comparative analyses revealed distinct microbial profiles across sample types, sand, eggshells, and hatchling tissues. Microbial transmission pathways appeared complex, with environmental sources, maternal cloacal fluids, and potentially external vectors. Fungal invasion into embryos was limited, likely due to natural eggshell defenses. This study underscores the complexity of microbial interactions in sea turtle nests and highlights the need for further research into microbial dynamics, particularly in conservation settings. Identifying key harmful and beneficial microbes may inform nest management strategies to improve hatchling survival in critically endangered hawksbill turtle populations.